Meningkatkan Kemampuan Memahami Dan Mendeskripsikan Jenis-Jenis Pasar Melalui Pembelajaran Kelompok Dengan Kegiatan Field Trip Siswa Kelas III SDN Kemayoran I Surabaya - Nurifah (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
This study aims to improve the learning outcomes of Social Studies (IPS) on the topic "Understanding and Describing Types of Markets" for third-grade students at SDN Kemayoran I Surabaya by applying a cooperative learning model with field trips. The research uses Classroom Action Research (CAR) methodology, conducted over two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. Before conducting the research, an initial survey was performed through observations and a pre-test to understand the actual classroom conditions. The findings from the first cycle indicated that 15 students had not yet achieved the Minimum Competency Criteria (KKM). Therefore, the research proceeded to the second cycle to improve the results further. The data analysis from the second cycle showed a significant improvement in student learning outcomes. The cooperative learning model with field trips effectively enhanced student interaction with peers and teachers, increased active participation, and encouraged students to respect others' opinions while freely and responsibly presenting material. The average score of the students in the final test of the first cycle was 73.9, whereas, in the second cycle, it increased to 83.4. Additionally, the percentage of students scoring above the KKM reached 91% in the second cycle. These results demonstrate that the cooperative learning model with field trips successfully enhances the learning outcomes of Social Studies on the topic of "Understanding and Describing Types of Markets" for third-grade students at SDN Kemayoran I Surabaya. The study concludes that implementing innovative and interactive learning methods can effectively address low student achievement and improve the quality of education in elementary schools. Future recommendations include the continuous use of such engaging and contextual teaching methods to achieve optimal learning outcomes for all students .